Heart Rate Measurement Using Non-invasive Sparse Signal Approach - Shuaibu, A.N. (Institute of Electrical and Electronics Engineers Inc., 2021)
High rate of occurrences of cardiovascular diseases has led to development of devices and systems that can measure and detect early warning symptoms of abnormalities. Recent studies show that cardiovascular diseases are the topmost leading cause of death, thus we need to detect symptoms of these diseases before they deteriorate. There is a need to develop systems that will monitor cardiovascular properties such as pulse rate and blood oxygen concentration. This will be very useful to people at high risks of cardiovascular ilness. In this paper, sparse representation technique has been used to monitor the heart rate using IP camera. The PPG signal is used to estimate the physical parameters using non-invasive camera. The result is compared with existing dictionaries such as discrete wavelet transform and discrete cosine transform for sparse signal reconstruction. The results show that the proposed method produced better performance Signal-to-Noise Ratio (SNR) as compared to the start-of-the-art methods. Â© 2021 IEEE.